Occurrence, health risk, and removal efficiency assessment of volatile organic compounds in drinking water treatment plants (DWTPs): An investigation of seven major river basins across China. (20th October 2022) - Zhang, Kunfeng; Chang, Sheng; Wang, Enrui; Zhang, Qi; Fan, Yueting; Bai, Yunsong; Zhang, Moli; Fu, Qing; Jia, Wenchao
Abstract: The presence of volatile organic compounds (VOCs) in drinking water has the potential to harm human health and undermine public confidence. Hence, this is the first study to comprehensively investigate concentrations of 25 VOCs in the 146 drinking water treatment plants (DWTPs) in 24 cities across seven major river basins (including the Yangtze River, Yellow River, Haihe River, Songhua River, Liaohe River, Pearl River, and Huaihe River), China. The occurrence, human health, and olfactory risks, as well as removal efficiency of VOCs in DWTPs, were evaluated. The findings revealed that 21 VOCs were detected, with concentrations ranging from not detected to 99.10 μg/L (trichloromethane). The maximum concentrations of trichloroacetaldehyde (54.90 μg/L) and trichloromethane (99.10 μg/L) exceeded China's regulated values (GB 5749–2006/2022). The concentrations of VOCs and water quality parameters showed a strong positive correlation. Human health and olfactory risks assessment indicated that drinking water exposures do not pose carcinogenic (CR < 10 −6 ) and non-carcinogenic (HI < 1) health risks to consumers, nor do olfactory and taste hazards (OHI <1). However, it is worth mentioning that due to the relatively high concentrations of some VOCs (trichloroacetaldehyde, acrolein, and trichloromethane), the health risk posed by them are still a major concern that needs to be addressed. Finally, the removal efficiency of VOCs is low in 146 DWTPs (mean of 12.91%–76.79%). Taken together, adding advanced treatment procedures for the purpose of improving the removal efficiency of pollutants of DWTPs in the future is an urgent priority. Graphical abstract: Image 1 Highlights: 21 VOCs were detected in 146 DWTPs of 24 cities from seven river basins of China. Water quality parameters were significantly positively correlated with VOCs. Health and olfactory risks, removal efficiency assessments simultaneously performed. Removal efficiencies of most VOCs in DWTPs ranged from 12.91 to 76.79%. VOCs detected cannot cause odor problems and little human health risks.